Automated Algorithm Configuration and Systematic Benchmarking for Heterogeneous MNK-Landscapes - Preuß, Oliver Ludger; Mensendiek, Carolin; Rook, Jeroen; Bossek, Jakob; Trautmann, Heike (Proceedings of the Genetic and Evolutionary Computation Conference, GECCO 2025, NH Malaga Hotel, Malaga, Spain, July 14-18, 2025)

Flexibles Addieren und Subtrahieren im Zahlenraum bis 100 - Häsel-Weide, Uta; Hußmann, S.; Nührenbörger, M. (Rechnen richtig lernen - flexibel, für alle und von Anfang an. Fachdidaktische Hintergründe und Lernangebote für die Grundschule)

Deep reinforcement learning for instance-specific algorithm configuration (GECCO Best Paper Award) - Schede, Elias; Seiler, Moritz; Tierney, Kevin; Trautmann, Heike (Proceedings of the Genetic and Evolutionary Computation Conference, GECCO 2025, NH Malaga Hotel, Malaga, Spain, July 14-18, 2025)

Die Ambivalenz von Sichtbarkeit. Ethische Perspektiven auf die digitale Transformation - Philippi, Martina

Grenzen des Verstehens - Philippi, Martina

Das Zentrum für KinderBildungsForschung als hybrider Ort der Vernetzung von Wissenschaft und Praxis im Grundschullehramtsstudium - Büker, Petra; Glawe, Katrin (Vernetzung in Hochschullernwerkstätten – einen Schritt weiter gehen. Bedingung, Mehrwert und Herausforderung)

Wie hängen Forschen, Partizipation und die Entwicklung von Nachhaltigkeit zusammen? Befunde aus Interviews mit forschungserfahrenen Kindern. Jahrestagung der Kommission Pädagogik der frühen Kindheit (PdfK) der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) mit dem Thema: Globale Krisen und Pädagogik der Frühen Kindheit. Freie Universität Bozen / Brixen. - Büker, Petra; Fernhomberg, Hannah Marie

Neue Wege in der Lehre: Primarstufenlehrkräftebildung im Kontext von Inklusion und Chancengerechtigkeit in der PrimOER-Community transformativ gestalten. Posterbeitrag an der 38. Jahrestagung der Inklusionsforscher:innen. Universität zu Köln. - Büker, Petra; Kamin, Anna-Maria; Oevel, Gudrun; Herding, Jana; Basten, Nina Celine; Bruhnke, Lorena; Henning, Charleen; Jaenke, Vanessa; Knurr, Moritz

„Inklusive, chancengerechte Bildung durch die Kooperation von Lehrenden verbessern? – Fragen und Perspektiven im Rahmen des Aufbaus einer OER-Community für die Primarstufenlehrkräftebildung“. Workshopbeitrag im Rahmen der BMBF-Vernetzungstagung: OER im Blick. Fördern. Vernetzen. Fortentwickeln. Jena. - Büker, Petra; Oevel, Gudrun; Herding, Jana; Bruhnke, Lorena

Effect of Strain Rate on the Deformation Behavior and Energy Absorption Characteristics of LPBF-Processed Ti2448 Microarchitectured Lattice Structures - Ghosh, Koustav; Milaege, Dennis; Steinmeier, Paul; Schaper, Mirko; Hoyer, Kay-Peter; Pramanik, Sudipta (Journal of Materials Engineering and Performance)

Gendersensible Bildung als Querschnittsaufgabe im Lehramtsstudium - Decker, Claudia; Möhwald, Aiko Julia; Uppenkamp, Vera; Westphal, Petra (Beiträge zur Schulentwicklung)

Wenn Gemeinden sich selbst organisieren. Evaluationsstudie - Reis, Oliver; Hofmeister, Lisa; Weber, Carla (PGR ohne amtliches Mitglied. Welche Konsequenzen hat der Rückzug von Hauptamtlichkeit aus der PGR-Arbeit für die Selbstorganisation des Gremiums? Modellraum 2)

PGR ohne amtliches Mitglied

Bajo el signo de la abducción: la investigación de lo fantástico en la narrativa policial argentina desde 1950 hasta la actualidad - Schmitz, Sabine (Diálogos con lo fantástico en el policial latinoamericano)

ANALYZING STUDENTS’INFORMAL APPROACHES TO CREATING DECISION TREES IN THE CLASSROOM - Fleischer, Franz Yannik; Biehler, Rolf (Proceedings of the 48th Conference of the International Group for the Psychology of Mathematics Education: Research Reports, Vol. 1)

Guaranteed-Quality Rational Bézier Guarding - Khanteimouri, Payam; Campen, Marcel (Computer-Aided Design)

Welches Wissen nutzen Studierende bei der Planung von Physikunterricht mit digitalen Medien? - Jordans, Melanie; Riese, Josef (Entdecken, lehren und forschen im Schülerlabor. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Bochum 2024)

Diálogos con lo fantástico en el policial latinoamericano

Trauma-Spuren und gefährdete Existenzen. Zu zwei Erzählungen Que Du Luus - Morrien, Rita (Literatur in Westfalen. Beiträge zur Forschung 21)

Morning clock gene expression in young adults of early and late chronotypes - Krueger, Bettina; Rajcsanyi, Luisa Sophie; Hundertmark, Katharina; Stutz, Bianca; Hinney, Anke; Buyken, Anette E. (Scientific Reports)
Abstract Variations in circadian rhythm-related genes influence the individual chronotype. Here, we hypothesize that the peak of clock gene expression at 7 a.m. differs between young adults with a late chronotype and young adults with an early chronotype. Participants of the Chronotype and Nutrition nutritional trial (ChroNu study) were selected for their chronotype assessed by the Munich Chronotype questionnaire (MCTQ) and actigraphy. Total RNA was isolated from CD14 + monocytes of participants at 7 a.m. on the run-in day. Expression levels of seven clock genes ( PER1 , PER2 , PER3 , NR1D1 , NR1D2 , CRY1 and CRISPLD2 ) of individuals with early ( n = 11) or late chronotypes ( n = 19) were analysed by reverse transcription quantitative polymerase chain reaction. Difference in expression levels was tested by Mann Whitney-U test. The relative expression levels of the selected genes were not significantly different between individuals with early and late chronotypes (all p > 0.07). Contrary to expectation, clock gene expression levels at 7 a.m. was similar in individuals with early and late chronotypes. Further studies on larger sample sizes with multiple sampling time points should elucidate whether gene expression is altered at other day times underscoring the biological difference between individuals with early or late chronotypes.